PAS staining of bronchoalveolar lavage cells for differential diagnosis of interstital lung disease - Zabel Peter; Hauber Hans P (BMC, 2009)
Abstract Bronchoalveolar lavage (BAL) is a useful diagnostic tool in interstitial lunge diseases (ILD). However, differential cell counts are often non specific and immunocytochemistry is time consuming. Staining of glyoproteins by periodic acid Schiff (PAS) reaction may help in discriminating different forms of ILD. In addition, PAS staining is easy to perform. BAL cells from patients with idiopathic pulmonary fibrosis (IPF) (n = 8), sarcoidosis (n = 9), and extrinsic allergic alveolitis (EAA) (n = 2) were investigated. Cytospins from BAL cells were made and cells were stained using Hemacolor quick stain and PAS staining. Lymphocytic alveolitis was found in sarcoidosis and EAA whereas in IPF both lymphocytes and neutrophils were increased. PAS positive cells were significantly decreased in EAA compared to IPF and sarcoidosis (25.5% ± 0.7% vs 59.8% ± 25.1% and 64.0% ± 19.7%, respectively) (P < 0.05). No significant correlation between PAS positive cells and inflammatory cells was observed. These results suggest that PAS staining of BAL cells may provide additional information in the differential diagnosis of ILD. Further studies ware warranted to evaluate PAS staining in larger numbers of BAL from patients with ILD.